2018
DOI: 10.1080/21646821.2018.1428461
|View full text |Cite
|
Sign up to set email alerts
|

Sleep EEG of Microcephaly in Zika Outbreak

Abstract: Microcephaly (MC), previously considered rare, is now a health emergency of international concern because of the devastating Zika virus pandemic outbreak of 2015. The authors describe the electroencephalogram (EEG) findings in sleep EEG of epileptic children who were born with microcephaly in areas of Brazil with active Zika virus transmission between 2014 and 2017. The authors reviewed EEGs from 23 children. Nine were females (39.2%), and the age distribution varied from 4 to 48 months. MC was associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Carvalho et al (2017) found hypsarrhythmia in EEGs of newborns infected by the Zika Virus and with microcephaly [ 1 ]. The presence of hypsarrhythmia in EEGs in the sleep of children with microcephaly was also found by Kanda et al (2018) [ 9 ]. It is worth mentioning that these works performed only the visual description of EEG signals due to the lack of mathematical and computational methods that can assist experts carrying out these types of tasks.…”
Section: Introductionsupporting
confidence: 60%
“…Carvalho et al (2017) found hypsarrhythmia in EEGs of newborns infected by the Zika Virus and with microcephaly [ 1 ]. The presence of hypsarrhythmia in EEGs in the sleep of children with microcephaly was also found by Kanda et al (2018) [ 9 ]. It is worth mentioning that these works performed only the visual description of EEG signals due to the lack of mathematical and computational methods that can assist experts carrying out these types of tasks.…”
Section: Introductionsupporting
confidence: 60%
“…An earlier study described EEG abnormalities in 62% of subjects with CZVS (similar to the proportion described here), including unilateral and bilateral interictal spikes, hypsarrhythmia and abnormal slow oscillations [11] . Another study also described a wide variety of epileptiform discharges, including hypsarrhythmia, slow waves, and fast runs of 4–12 Hz (usually 6 Hz) [12] . However, none of those previous studies demonstrated the existence of correlations between clinical, structural, and electroencephalographic findings.…”
Section: Discussionmentioning
confidence: 98%
“…Congenital syphilis and toxoplasmosis also lead to EEG abnormalities, including hypsarrhythmia [10] . Recent reports described that ZIKV infection during pregnancy could also lead to seizures and epilepsy in approximately half of the cases [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,27,31,35,36,42,45,46,48,50,51,FIGURE 2 | Zika studies reviewed by year of publication and country of origin. 54, 56, 61, 62, 66, 69-71, 74, 77).…”
mentioning
confidence: 99%